ON VIRTUAL MODELLING OF A TRANSVERSAL COUPLING WITH LINKAGES - GAVRILA Cornel Catalin; VELICU Radu (Annals of the Oradea University: Fascicle Management and Technological Engineering, 2015)
Mechanical structures virtual modeling, as multibody systems with a minimal bodies number, in the real time simulation of product dynamic behavior is a necessity. For a company, it saves time in product developing, reduces the number of physical prototypes and experiments, reduces the prices of product and increases the newly developed product quality. In the paper there are presented some aspects regarding the modeling of a transversal coupling with linkages, as a multibody system, using ADAMS. In the paper first part, there is presented the coupling, parts, geometry and virtual modeling. Then are defined the geometrical and kinematical restrictions between the coupling model parts. In the paper second part, there are presented aspects about the simulation and the results. In the paper final part, there are presented the conclusion.